Acne Peel Off Mask Formulation From Bitter Melon Extract (Formulasi Masker Peel Off Antijerawat dari Ekstrak Buah Pare) - Ningsih, Wida; Agustriliana, Lativa; Novrita, Sisri (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2024)
Flavonoids, alkaloids and saponins are secondary metabolite compounds contained in bitter melon plants and compounds that act as antibacterials. One of the causes of acne is caused by the bacteria Propionibacterium acnes. To reduce acne caused by bacteria by using skin care products such as peel-off masks. To utilize bitter melon which is still limited to its use only for food ingredients. This study made a peel mask from bitter melon extract to inhibit or kill the growth of bacteria that cause acne. Bitter melon extract was obtained using 96% ethanol solvent in the maceration extraction process. Peel-off masks were made with three variations of bitter melon extract concentration, namely 5%, 10% and 15%. After the peel-off mask was formed, a physical evaluation and antibacterial activity test were carried out against Propionibacterium acnes. Physical evaluation of the peel-off mask included organoleptic, pH, drying time test, spreadability and irritation test. The results of the physical evaluation of the bitter melon peel-off mask included showing results that had met the standard requirements for peel-off masks. The results of the antibacterial activity test at a concentration of 5%; 10%; and 15% showed almost the same inhibition zone, namely 8.22 mm, 8.29 mm and 8.53 mm. Based on the inhibition zone, the antibacterial activity of the bitter melon peel-off mask is included in the moderate category and it is concluded that bitter melon can be formulated as an anti-acne peel-off mask.